IMPROVING THE TEACHING OF THE SUBJECT "COMPUTER TOOLS IN LINGUISTIC RESEARCH" BASED ON SOFTWARE TOOLS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the issues of creating multimedia presentations based on modern software tools and organizing classes using them in teaching the subject "Computer tools in linguistic research" in the educational direction of the higher educational institution "Computer Linguistics".